Khung trình độ Quốc gia Việt Nam đối với các trình độ Thạc sĩ và Tiến sĩ (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Khung trình độ Quốc gia Việt Nam đối với các trình độ Thạc sĩ và Tiến sĩ